Differential Pressure Transducer for Corrosion Monitoring of Iron - Yadav, Amar Prasad (International Journal of Applied Sciences and Biotechnology, 2014)
In this study, differential pressure transducer (DPT) has been applied as an alternate corrosion monitoring device for monitoring corrosion of iron in atmospheric environment by measuring very small changes in the amount of oxygen. The result of corrosion current obtained from DPT method has been compared with that obtained from AC impedance method. The difference in the value of corrosion current obtained from these two methods was attributed to the error in choosing the value of proportionality constant k of the Stern-Geary equation. DOI: http://dx.doi.org/10.3126/ijasbt.v2i1.10112 Int J Appl Sci Biotechnol, Vol. 2(1): 109-111